Cytotoxic sesquiterpenoid quinones from South China Sea sponge Dysidea sp. Issue 17 (19th August 2021) - Luo, Xiangchao; Li, Pinglin; Wang, Kunya; de Voogd, Nicole J.; Tang, Xuli; Li, Guoqiang
Abstract: A new sesquiterpene, (+)-19-methylaminoavarone (1 ), together with six known compounds (2 –7 ), were isolated from the Xisha Islands marine sponge Dysidea sp. The structures were elucidated based on their spectroscopic data. We revised the carbon spectrum data of the compound 2 . The absolute configurations of compounds 1 and 2 were further confirmed by electronic circular dichroism (ECD) analysis. Compounds 1 –3 and 5–7 showed potent cytotoxic activity against several human cancer cell lines. Abstract : UF0001